Saberes mobilizados pelo professor de matemática na educação de jovens e adultos: buscando fios que tecem esta relação - Scherwenske, Lisiane Jaques Rodrigues (2013)
This paper is the description of the research project Knowledge mobilized by the Mathematics teacher in adults and youths education: searching for what weaves this relationship together which has investigated: How does the teaching knowledge permeate the teaching performance of the Mathematics lecturer in adults and youths education? To answer this question strategic methods have been utilized, such as the semi-structured interview, as well as the focus groups and lookalike replacement techniques. The project is about a qualitative study of character developed in a local school in Pelotas, in which Mathematics teachers working in the adults and youths education field have been the studied group. Theoretical references about teaching knowledge which weaves the teachers performance have been searched in the concepts of Tardif (2012) and Gauthier et al. (1998). To answer the research issue, the results of the semi-structured interview and the lookalike replacement technique have been analyzed by using the technique of content analysis. The information that has come from the focus group subsidized the formation of the final product: a website, which intends to contribute to the teaching performance of Mathematics teachers who work with adults and youths.